Urban water dissipation calculation based on the improved water balance models. Issue 1 (13th April 2021) - Zhou, Ke
Abstract: The urban water dissipation models are developed based on observation and different urban construction patterns. The regional water dissipation is selected in Zhengzhou, the capital city of Henan Province, China. According to model calculation results, the annual water dissipation was obtained (820.0 mm), which is significantly higher than that compared with the traditional methods (494. 4 mm). The results show that the water dissipation contribution rate of green space, inside building, hardened ground and pavement, and water surface are 40.58, 38.70, 18.32, and 2.40%, respectively. The water dissipation of hardened ground and pavement, green space, and water surface is greatly influenced by hydrological and meteorological factors. The water dissipation inside a building is proportional to the number of building layers and residents. The results show that water dissipation inside a building cannot be ignored and it is the main component of artificial water dissipation. Under the same rainfall conditions, the water dissipation of the hardened ground and pavement is inversely proportion to the runoff coefficient. HIGHLIGHTS: Urban water dissipation was classified according to different urban facilities. Water dissipation models were proposed based on different urban water dissipation sectors. The water dissipation contribution rate of different urban facilities was calculated. The results will be an important technical support for urban water planning and utilization. Graphical Abstract